(1)-p^2×(-p)^4×【(-p)^3】^5
1个回答
1)-p^2×(-p)^4×【(-p)^3】^5=p^21
(2)(m-n)^2×【(n-m)^3】^5=(n-m)^17
(3)2^5×8^4×16^2=2^25
相关问题
P(AB)=P(A)×P(B)=0.05,P(AC)=P(A)×P(C)=0.1,P(BC)=P(B)×P(C)=0.1
如何把这些打出来?9(p-q)平方-6p+6q+1 =[3(p-q)]²-2×[3(p-q)]×1+1²
P(A)×P(B)=0.05,P(A)×P(C)=0.1,P(B)×P(C)=0.125.求P(A)/P(B)/P(C)
p△q=4×q(P+q)÷2,求5△(6△4 )
计算:(2p^5)^3*(-p)^3+4*(-1/2p^5)^2*[(-p)^2]^4
分解因式:(p²+q²)²-4p²q²=____________1.25×14²-125×8.6²
p1,p2,p3为质数,P1=5,5P2P3=5(5+P2+P3),则P2=?,P3=?p1,p2,p3为质数,P1=5
设p、q是两个数,规定:p△q=3×p-(p+q)÷2,求7△(2△4).
问六上寒假新时空P34页. 如果:△×☆=3/2 △×□=4/5 □×3/4=6 那么:△=() ☆=() □=()
在横线里填上“>”、“<”或“=”.1o9×p______o二二 5二×7______7二×5 5二6×p______2